The Influence of Manipulative Media on Enhancing Mathematical Representation Skills of Fourth Grade Elementary School Students - Putri, Rasya Aginta Najwa Setiawan; Istiana, Yuyun; Anggraini, Meylisa; Wiryanto, Wiryanto; Habibie, Ramadhan Kurnia (IKIP PGRI Bojonegoro, 2025)
This study aims to analyze the influence of using manipulative media on enhancing the mathematical representation skills of fourth-grade elementary school students. A quasi-experimental method with a pretest-posttest control group design was used. The research was conducted at SDN Sumberwuluh 1 Mojokerto, with a sample of fourth-grade students divided into experimental and control groups. Data were collected through mathematical representation ability tests, teacher and student activity observation sheets, and documentation. The results showed that manipulative media had a significantly positive effect on students' mathematical representation skills. The experimental group exhibited higher improvement than the control group, with an average N-Gain Score of 0.71 (high category). Aspects of students' visual, symbolic, and verbal representation experienced significant improvement. In conclusion, manipulative media helps students connect abstract concepts with concrete representations, facilitating a deeper understanding of mathematics.